2010
DOI: 10.1158/1940-6207.capr-09-0173
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Fish Oil on the Chemopreventive Efficacy of Tamoxifen against Development ofN-Methyl-N-Nitrosourea–Induced Rat Mammary Carcinogenesis

Abstract: The antiestrogen tamoxifen reduces breast cancer incidence in high-risk women but is unable to inhibit the development of hormone-independent tumors. Omega-3 polyunsaturated fatty acids (n-3 PUFA), known ligands of the peroxisome proliferator activated receptor-γ (PPARγ), generally exert tumorsuppressive effects. Based on the known crosstalk between the estrogen and the PPARγ receptors, we tested the hypothesis that the combination of tamoxifen with n-3 PUFA results in a superior antitumor action over the indi… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
53
0
1

Year Published

2011
2011
2016
2016

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 35 publications
(60 citation statements)
references
References 34 publications
(35 reference statements)
6
53
0
1
Order By: Relevance
“…diet), mammary cancer incidence, cancer multiplicity, and cancer burden per rat were significantly reduced. Tamoxifen is known to cause a modest decrease in rate of body weight gain (36), and this was observed; however, the n-3: n-6 ratio had no effect on grow rate.…”
Section: Methodsmentioning
confidence: 96%
“…diet), mammary cancer incidence, cancer multiplicity, and cancer burden per rat were significantly reduced. Tamoxifen is known to cause a modest decrease in rate of body weight gain (36), and this was observed; however, the n-3: n-6 ratio had no effect on grow rate.…”
Section: Methodsmentioning
confidence: 96%
“…The set point is manually adjusted and kept as low as possible to obtain the best resolution while the total force applied on the sample during the imaging is approximately 300 pN as measured by force-distance curve. The 512x512 pixel 2 images are recorded at typical scan frequencies of 4-6 Hz. AFM images are flattened using the SPMLab NT Ver.…”
Section: Afm Imagingmentioning
confidence: 99%
“…The main dietary sources of eicosapentaenoic (EPA, 20:5n-3) and docosahexaenoic acid (DHA, 22:6n-3) are cold-water fish oils. Epidemiological studies have suggested that an increased n-3 PUFA intake might be associated with a reduced breast cancer incidence in humans [1][2][3]. A number of mechanisms have been proposed for the anticancer actions of n-3 PUFA, including suppression of neoplastic transformation, inhibition of cell proliferation, enhancement of apoptosis, and antiangiogenic action.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, within the polyunsaturated fatty acids the ratio of n-3: n-6 fatty acids was varied from 25:1 to 1:25 to provide a robust evaluation of the role of this ratio in affecting the postinitiation phase of 1-methyl-1-nitrosourea (MNU)-induced mammary carcinogenesis in the rat (4). Our laboratories were the first to show that the combination of n-3 fatty acids with Tamoxifen was a more effective chemopreventive regimen than the individual interventions (4,9). Specifically, we observed that high n-3:n-6 ratios (10:1 and 25:1) were able to suppress carcinogenesis in Tamoxifentreated animals, thus suggesting that they are able to inhibit the development of hormone-resistant tumors.…”
Section: Introductionmentioning
confidence: 99%